Gene and protein expression of myosin heavy chain in Nellore cattle comparing growth or meat tenderness traits - Chardulo, L. A.L. [UNESP]; Baldassini, W. A. [UNESP]; Curi, R. A. [UNESP]; Pereira, G. L. [UNESP]; Machado Neto, O. R. [UNESP]; Dal-Pai, M. [UNESP]; Vechetti-Júnior, I. J. [UNESP]; Malheiros, J. M.; Enriquez-Valencia, C. E. (Taylor & Francis, 2019)
The objective was to investigate gene and protein expression of myosin heavy chain (MyHC) in Nellore cattle slaughtered at different weights (BW) or degrees of meat tenderness. Ninety animals with initial BW 370 ± 37 kg, 24 months of age, were slaughtered after 95 days on feed. We evaluated shear force (SF), myofibrillar fragmentation index, ribeye area, backfat thickness, marbling, color, and cooking losses. Subsequently, 24 animals were selected and divided into four contrasting groups, in which light (BW = 504.58 ± 32.36 kg) versus heavy animals (BW = 604.83 ± 42.97 kg) and animals with tender (SF = 3.88 ± 0.57 kg) versus tough meat (SF = 7.95 ± 1.04 kg) were compared. The MYH7, MYH2 and MYH1 genes were analyzed by real-time PCR. The MyHC isoforms (MyHC-I, MyHC-IIa, and MyHC-IIx) were quantified by SDS-PAGE electrophoresis. We found lower expression of MYH2 and MYH1 genes in heavy compared to light animals and a higher amount of MyHC-I isoform in the tough meat group compared to the tender meat group. Protein expression of MyHC-IIa was higher in the tender meat group. A negative correlation was found of this protein and SF (tenderness), suggesting MyHC-IIa as a biomarker of meat quality.
Keywords: Biochemistry; Bos indicus; candidate gene; meat science; muscle fibers